2020
DOI: 10.1021/acs.energyfuels.0c01909
|View full text |Cite
|
Sign up to set email alerts
|

A Nitrogen-Doped Carbon Matrix Aiming at Inhibiting Polysulfide Shuttling for Lithium–Sulfur Batteries

Abstract: Lithium−sulfur (Li−S) batteries have been attracting great attention as promising rechargeable batteries because of their large specific capacity and high energy density. However, some technical problems still limit the commercialization value of Li− S batteries such as poor electrical conductivity, shuttle effects, and volume expansion. To overcome the aforementioned issues, Ndoped carbon composites were synthesized via a one-step hydrothermal method. To obtain different N-doping configurations, a carbon prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 48 publications
0
18
0
Order By: Relevance
“…Most recently, it was observed that the Li–S batteries are a potential candidate for energy-storing devices due to their excellent energy density, indigenously available sulfur material, and low cost . Currently, researchers are focused on nanostructured composite materials and the development of battery design of Li–S batteries toward commercial application in electrochemical energy storage devices. Kang et al proposed a facile method for the synthesis of hierarchical porous activated carbon from coal having a high surface area of 3343 m 2 g –1 , which is beneficial for polysulfides while also increasing sulfur loading. As can be observed in Figure , the coal-derived hierarchical porous activated carbon had a high specific capacity of 1390 mAh g –1 at 0.05 C, as well as outstanding rate performances and cyclic stability.…”
Section: Coal-derived Activated Carbon As Electrode Materials For Li–...mentioning
confidence: 99%
“…Most recently, it was observed that the Li–S batteries are a potential candidate for energy-storing devices due to their excellent energy density, indigenously available sulfur material, and low cost . Currently, researchers are focused on nanostructured composite materials and the development of battery design of Li–S batteries toward commercial application in electrochemical energy storage devices. Kang et al proposed a facile method for the synthesis of hierarchical porous activated carbon from coal having a high surface area of 3343 m 2 g –1 , which is beneficial for polysulfides while also increasing sulfur loading. As can be observed in Figure , the coal-derived hierarchical porous activated carbon had a high specific capacity of 1390 mAh g –1 at 0.05 C, as well as outstanding rate performances and cyclic stability.…”
Section: Coal-derived Activated Carbon As Electrode Materials For Li–...mentioning
confidence: 99%
“…As seen in Figure a, after 1000 cycles, the cell still has a discharge capacity of 310 mAh g –1 at 1 A g –1 . These results show the extraordinary ability of NC-5 to reduce shuttle effects . As a result, the carbon host with polar affinity may absorb a variety of S-containing compounds.…”
Section: Polar Composite Cathode Materialsmentioning
confidence: 84%
“…Generally, the sulfur cathode in the Li–S battery would experience reversible multielectron reactions (i.e., S 8 + 2Li ↔ Li 2 S 8 ↔ Li 2 S 8– x + Li 2 S x ↔ Li 2 S 2 → Li 2 S), in which the lithium polysulfide (Li 2 S x , 4 ≤ x ≤ 8) can be dissolved into the electrolyte and migrated to the side of lithium metal anode, causing the irreversible reaction to form Li 2 S (Figure b). , As a result, the Li–S batteries always suffer from several notorious issues: (i) a low utilization efficiency of sulfur and sulfur-derived products (i.e., Li 2 S x ), because of the nonconductive nature; , (ii) severe capacity fading that is caused by the Li 2 S x shuttle effect, which can decrease the Coulombic efficiency significantly; , and (iii) the safety issue of lithium dendrites, which can be formed upon the cycling when the lithium metal anode was applied . To solve the problematic issue, the research in Li–S batteries can be summarized as described below: (i) engineering sulfur electrodes that are modified and coated with different types of materials (e.g., carbon, , polymer, , metal oxide, , etc.)…”
Section: Introductionmentioning
confidence: 99%